1986
DOI: 10.1111/j.1365-2052.1986.tb03197.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in blood proteins within and between Spanish dairy sheep breeds

Abstract: Eleven flocks of three Spanish sheep breeds have been studied: four Churra, four Lacha and three Manchega. Genetic variations between flocks of the same and different breeds have been analysed, using eight genetic blood systems and a wide range of statistical methods. The results show that the Churra, Lacha and Manchega breeds present significant differences between each other. Significant intraracial variations have been observed in Churras and Lachas, although they were almost non-existent in Manchegas. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 15 publications
1
5
0
4
Order By: Relevance
“…Sánchez Belda, Tejón, Aparicio Macarro, Sierra, Herrera y Sotillo, todos ellos continuadores en la descripción fenotípica de las razas españolas, esfuerzo que se ha visto plasmado en múltiples publicaciones de relevancia (Sánchez Belda y col. 1974, 1981, 1984, 1986Tejón. En nuestro país, desde los años 20 se creó una corriente de importantes etnólogos que estudiaron y divulgaron las características de las razas españolas.…”
Section: Discussionunclassified
“…Sánchez Belda, Tejón, Aparicio Macarro, Sierra, Herrera y Sotillo, todos ellos continuadores en la descripción fenotípica de las razas españolas, esfuerzo que se ha visto plasmado en múltiples publicaciones de relevancia (Sánchez Belda y col. 1974, 1981, 1984, 1986Tejón. En nuestro país, desde los años 20 se creó una corriente de importantes etnólogos que estudiaron y divulgaron las características de las razas españolas.…”
Section: Discussionunclassified
“…Different authors have reported different values of D in different sheep breeds. Ordas and Primitivo (1986) estimated the genetic distance between Spanish dairy sheep breeds and reported 0.0094-0.055 using data from 8 loci. Zanotti et al (1990), using data from four blood groups and six protein loci, reported genetic distance ranging between 0.012 and 0.060 in five Italian sheep breeds.…”
Section: Genetic Distance and Genetic Identitymentioning
confidence: 99%
“…For example, Spanish sheep (Ordas and San Primitivo, 1986;Rodero et al, 1982), Dutch sheep (Buis and Tucker, 1983), and Italian sheep (Zanotti Casati et al, 1988 have been investigated based on allele frequency data for blood groups and blood protein and enzyme polymorphisms. In Asia, a similar study has been conducted for indigenous Indian sheep (Singh et al, 1979).…”
Section: Introductionmentioning
confidence: 99%